Completion and publication of clinical trials in a cooperative group: a cohort study of trials of the Swiss Group for Clinical Cancer Research (SAKK) - Benjamin Kasenda; Miklos Pless; Beat Thürlimann; Stefanie Hayoz; Annina Lea Schenker; Christoph Kopp; Sämi Schär; Roger von Moos (BMJ Open, 2023)
Background Premature trial discontinuation and non-publication of trial results are still major issues negatively affecting reliable evidence generation.Objectives To investigate trial completion and publication rate of cancer trials conducted within the Swiss Group for Clinical Cancer Research (SAKK).Design Cohort study of clinical trials.Setting Cohort of interventional cancer trials conducted in Switzerland with accrual closure between 1986 and 2021 identified from the SAKK trial management system.Outcomes Premature trial discontinuation and publication in peer-reviewed journal.Results We included 261 trials; median number of recruited patients was 150.5 (range 1–8028). Most trials (67.0%) were randomised. Overall, 76 of 261 (29.1%) trials were prematurely closed for accrual. The three main reasons for premature closure were insufficient accrual in 28 trials, followed by stopping for futility in 17 or efficacy in 8 trials. We included 240 trials for the publication status (21 excluded, because 8 still in follow-up, for 10 the primary completion date was less than a year ago and for 3 the manuscript was submitted, but to accepted yet). 216 of 240 (90.0%) were published as a full article, 14 were published in other formats, leading to an overall publication rate of 95.8%. The rate of premature discontinuation declined over time, with 34.2%, 27.8% and 23.5% in trials activated before 2000, between 2000 and 2009, and since 2010, respectively. We observed an increasing publication rate in peer-reviewed journals over time: 79.2% (closed before 2000), 95.7% (closed between 2000 and 2009) and 93.2% (closed after 2010).Conclusion Insufficient patient recruitment is still the major reason for premature trial discontinuation. SAKK has continuously improved its quality management of trial conduct over time leading to increased successful trial completion and publication. However, there is still room for improvement to increase the number of trials reaching their target sample size.